Problems in Implementing the Curriculum Merdeka - Etty Octaviani Manalu; Saveria Mote; Sofia Pasaribu; Maya Pujowati; Tri Suwarningsih (Journal of Educational Learning and Innovation (ELIa), 2026)
The Independent Curriculum is a new policy launched by the Ministry of Education, Culture, Research, and Technology in 2022 to create more flexible, contextual, and student-centered learning. This curriculum provides educational units with the flexibility to design learning tailored to student needs. However, various obstacles remain in its implementation. This study aims to identify the problems facing the implementation of the Independent Curriculum at SDN Inpres Perumnas IV, Jayapura City, analyze the causes, and describe the efforts made to address them. The method used was descriptive qualitative, with data collection techniques including interviews, observation, and documentation. The results indicate that teachers experience difficulties understanding curriculum concepts and developing open modules, as well as limited training and learning resources. Furthermore, limited infrastructure and resources also pose obstacles to implementing the Independent Curriculum in schools. Efforts undertaken by schools include independent training, utilization of the Independent Teaching Platform, learning communities, and internal collaboration. This study emphasizes the importance of strengthening teacher competencies as a key to successful curriculum implementation, as well as the need for adaptive policy support for educational units.